Survival after myocardial infarction according to left ventricular function and heart failure symptoms - Jarle Jortveit; Peder L. Myhre; Kristian Berge; Sigrun Halvorsen (ESC Heart Failure, 2025)
Abstract Aims Left ventricular (LV) dysfunction following acute myocardial infarction (AMI) is common even in the absence of signs and symptoms of heart failure (HF). Recent trials of patients with LV dysfunction post‐AMI have demonstrated low event rates during follow‐up. We aimed to assess the real‐world prevalence and outcomes post‐AMI, stratified by LV ejection fraction (LVEF) and the presence or absence of HF symptoms. Methods and results Cohort study of patients with AMI registered in the Norwegian Myocardial Infarction Registry 2013–2022. Outcomes were short‐ and long‐term all‐cause mortality. Mortality was assessed by Kaplan–Meier survival curves, Life Table and multivariable Cox regression models. Results Among 70 809 AMI patients (mean age 68.1 ± 12.9 years, 31% female), preserved (≥50%), mildly reduced (41%–49%) and reduced (≤40%) LVEF were present in 63.5%, 23.2% and 13.3%, respectively. Symptomatic HF was present in 3.3%, 28.1% and 63.2% of patients with preserved, mildly reduced and reduced LVEF. For each LVEF category, 1‐year cumulative mortality rate from discharge was 3.9%, 7.8% and 17.8% for asymptomatic, and 16.2%, 13.7% and 20.2% for symptomatic patients, respectively. Symptomatic patients discharged alive had higher risk of mortality than asymptomatic: adjusted hazard ratio 1.85 (1.70–2.02) for preserved LVEF, 1.33 (1.25–1.41) for mildly reduced LVEF and 1.15 (1.06–1.24) for reduced LVEF. Conclusions Reduced LVEF in the acute phase of AMI was associated with up to 20% 1‐year mortality after discharge, substantially higher than in recent post‐MI trials. Symptoms of HF during the index hospitalization were associated with worse outcomes in patients with preserved LVEF but contributed little additive risk for patients with reduced LVEF.